2002
DOI: 10.1007/s11664-002-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Pad effects on material-removal rate in chemical-mechanical planarization

Abstract: INTRODUCTIONAmong the newly developed planarization technologies for ultra-large-scale integration metallization, chemical-mechanical planarization (CMP) has emerged to be most promising because it can provide better local and global planarization of the wafer surface. 3 In recent years, CMP has emerged as an enabling technology for the next generation of chip manufacturing and has become the second fastest growing area of semiconductor-equipment manufacturing. Beside interlayer-dielectric planarization, CMP h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 9 publications
2
58
1
Order By: Relevance
“…negative) particle diameters. The general behavior illustrated in Figure 1 follows from the fact that the total number of particles entrapped beneath a pad asperity is inversely proportional to the mean particle size (diameter) to the third power [4]. Thus, even though larger mean particles remove more material individually, there are far fewer of them.…”
Section: Mrr Model With Identical Height Pad Asperities (Based On Modmentioning
confidence: 95%
See 1 more Smart Citation
“…negative) particle diameters. The general behavior illustrated in Figure 1 follows from the fact that the total number of particles entrapped beneath a pad asperity is inversely proportional to the mean particle size (diameter) to the third power [4]. Thus, even though larger mean particles remove more material individually, there are far fewer of them.…”
Section: Mrr Model With Identical Height Pad Asperities (Based On Modmentioning
confidence: 95%
“…Many models have been proposed to investigate the mechanisms of material removal in the CMP process. Features considered, include statistics of pad asperity height and spatial distribution [1], local deformation of individual cells [2], elastic contact between the wafer and the pad [3], and multi-level contact evolution at particle and asperity scales, leading to several domains of wafer/particle/pad contact [4]. Fu and Chandra [5] investigated the effects of viscoelastic pad properties on the material removal rate (MRR).…”
Section: Introductionmentioning
confidence: 99%
“…The polishing pad is highly deformable porous solid with complex topology [24,25]. A modeling framework should embrace these unique geometric and kinematics features, even with an effective mean representation.…”
Section: Mechanistic Process Modeling For Materials Removal Ratementioning
confidence: 99%
“…Fu et al [12] showed another nonlinear MRR model based on the concept of incomplete and complete contact between the wafer and the pad (beam bending model of pad). Bastawros et al [46] presented a model considering several saline features of the pad, such as the pad asperity of various amplitudes and frequencies, the local deformation of individual cells, the elastic asperity contact between the wafer and the pad, the multilevel contact evolution at the particle size scale, and the macro asperity scale. These factors lead to several domains of waferparticle-pad contacts.…”
Section: Review Of Modeling Of Pad Effects On Polishing Performancementioning
confidence: 99%